Using Inquiry Strategy in Teaching Social Studies to Develop Metacognitive Studies among Second Grade Intermediate Students - Alghedani, Noier Hamdan (Journal of Curriculum and Teaching Methodology, 2023)
This study aims at identifying the effectiveness of using inquiry strategy in developing metacognitive skills among second intermediate class students in Madina, Saudi Arabia.To achieve this, the researcher employed a quasi-experimental design to a study sample consisting of (67) students from the 20th Intermediate School students in Medina. The sample was chosen and divided randomly. It was divided into two groups: the first is the experimental consisting of (33) female students who studied using the inquiry strategy, and the second is a control group consisting of (34) female students who studied using the traditional way. The researcher prepared a guide for the teacher to teach students using the inquiry strategy. The tool for metacognitive skills was prepared. By conducting pre and post tests and comparing them statistically according to their procedures, the researcher reached the findings of the study. There is a statistically significant difference at the level (0.05) between the mean scores of students of the experimental group and the control group in the post application of test the metacognitive test separately and collectively as a whole in favor of the experimental group. The findings indicated the effectiveness of using the inquiry strategy in developing metacognitive skills for the second intermediate school students, with a large effect size based on the value of the standard effect size for the difference between the experimental and control groups’ scores in the post-application. In the light of these findings, the researcher recommended a number of recommendations, the most important of which were: paying attention to using the inquiry strategy in the educational process due to its effectiveness in developing metacognition understanding skills of students, in addition to the necessity of establishing training courses for teachers that contribute to increasing their experiences and their ability to use strategies based on problem solving while learning.